GASTROESOPHAGEAL REFLUX IN NEWBORNS AND INFANTS (II) - Valeriu V. Lupu; Ancuta Ignat; Gabriela Paduraru; Marin Burlea (Amaltea Medical Publishing House, 2016)
Gastroesophageal reflux in newborns and infants is particularized by pathogeny, diagnosis and therapeutical approach, functional immaturity of the digestive tract, the anatomic immaturity of the Hiss lower esophageal sphincter and lower gastric acidity. In infants, the low compliance with the laborious procedures such as pHmetry, impedance - pH-metry and digestive endoscopy is also considered. The border between regurgitations, physiological gastroesophageal reflux and the reflux disease is sometimes hard to establish. Changing the lifestyle of infants (feeding and position changes) based on the mother's compliance with the medical recommendations is a first step in the treatment of GER, followed in non-responsive cases by pharmacological therapy and surgery.